Teaching kit for art teachers: Impasto (T-Kat: Impasto) / Norfarah Nadiah Mohd Fadzilah - Mohd Fadzilah, Norfarah Nadiah (2014)
This research examines the teaching process of Visual Art Education particularly on the topic of impasto technique at one of the secondary school in Kuantan, Pahang. The sample of this research is the Head of Visual Art Education teacher of the school. From the preliminary findings, there were inadequacies in the teaching process. The teacher did not emphasize on art values and art disciplines. The teaching process was not really interesting since the teacher only used verbal teaching without any media interactive assistance. Furthermore, the teacher also lacks the skills in teaching the Impasto technique. There were no exposure on the appropriate tools and materials during teaching and hence the Impasto technique was not taught as it should be. This is due to the low budget provided for the subject. Moreover, the cost of materials and tools for Impasto technique were too expensive. Therefore, this research developed instructional resources called a "teaching kit" and it has been developed based on the Discipline Based Art Education (DBAE) model whereby it is a combination of various art disciplines of teaching. For instance, the art disciplines are consists of art production, art history, art criticism and art appreciation. By having these disciplines in this Visual Art Education, the three learning domains which are cognitive, affective and psychomotor can be enhanced among the students. In order to collect and analyze the data, the observation and interview were conducted at the preliminary stage of this research. It was also conducted after the teacher has adopted the teaching kit into the teaching process as the objective of this research was to examine the effectiveness on the usability of teaching kit on the Impasto teaching. The post findings showed that the teacher was satisfied with the teaching kit since it helped the students to improve their cognitive, affective and psychomotor skills by having adequate content and wellstructured steps with regards to the Impasto technique. The students has been exposed to the artwork by top painters of Impasto, how to critic an artwork in steps, how to use the materials and tools in producing an artwork using Impasto technique, and how to appreciate the said artworks. The use of interactive media such as PowerPoint slide presentations helped the students become more focus and attentive during the learning process hence enhance their understanding towards the Impasto technique. The video demonstration on the Impasto technique was displayed during class activities during artwork production and this was also very useful to the teacher that was lacking the skill in this Impasto technique. The students were exposed on how to use the appropriate tools and materials for Impasto technique such as pallet knife, oil paints, canvas, and linseed oil during artwork production.